The Davos Debate and essence of man - Cortés García, Francisco Joaquín (Con-Textos Kantianos. International Journal of Philosophy, 2025)
The paper explores the philosophical debate between Ernst Cassirer and Martin Heidegger at the 1929 Davos Conferences, focusing on their divergent conceptions of the human being. Cassirer, from a Neo-Kantian perspective, emphasizes culture and symbols as key elements for understanding human experience. Heidegger, on the other hand, through his concept of Dasein, concentrates on individual existence, finitude, and authenticity. The debate, which took place in a context of intellectual and political crisis in interwar Europe, marked a bifurcation in the history of philosophical thought, revealing a clear divergence in the idea of man. The analysis also draws parallels between this debate and the characters in Thomas Mann’s novel The Magic Mountain, highlighting the influence of these ideas on 20th-century philosophical and cultural thought.